Cytokine and reactivity profiles in SLE patients following anti-CD19 CART therapy - Daniel Nunez; Darshil Patel; Jenell Volkov; Steven Wong; Zachary Vorndran; Fabian Müller; Michael Aigner; Simon Völkl; Andreas Mackensen; Georg Schett; Samik Basu (Molecular Therapy: Methods & Clinical Development, 2023)
Chimeric antigen receptor (CAR) T cells targeting CD19+ B cells have demonstrated efficacy in refractory systemic lupus erythematosus (SLE). Although initial clinical data suggest that anti-CD19 CAR T cell therapy is well tolerated and highly effective, the immunologic consequences of CAR T cell therapy in SLE patients remain unclear. We profiled serum in six refractory SLE patients prior to and 3 months following CAR T cell infusion. Three months post T cell infusion, the inflammatory cytokines IL-6 and TNFα decreased in patient sera. This was accompanied by elevations in serum IL-7 and BAFF. Furthermore, SLE-associated antibodies dropped profoundly in five of six patients. Last, consistent with other reports of CD19 CAR T therapy in B cell malignancies, we were able to show marginal impact of anti-CD19 CART therapy on pre-existing humoral immune responses in SLE patients. Together, these results provide insights into the mechanisms of efficacy of anti-CD19 CAR T cell therapy in SLE.